Holocene land degradation and climatic change in northeastern Iceland - Olafsdottir, Rannveig; Guomundsson, HJ (The Holocene, 2002)
The spatial and temporal pattern of land degradation in northeastern Iceland during the Holocene is analysed in relation to climatic fluctuations. Tephrochronology is used to date the infer-red terrestrial changes. and remote sensing and geographical information systems to assess the dynamic relationships between topographic relief. geomorphic processes and soil structure. Changes in vegetation and soil cover during the Holocene are found to he more dynamic than previously reported, highlighted by three substantial degradation phases, two of which occurred prior to the recorded Viking settlement in the ninth century AD, c. 5000 BP and c. 2500 BP. The results demonstrate the role of climate in modifying land cover, hence triggering land degradation without anthropogenic influence. However, anthropogenic activity probably had a significant role in the acceleration of the third degradation phase in the sixteenth century AD, when the system was possibly forced beyond its threshold of recovery, resulting in land degradation on a catastrophic scale.